Identification of intrinsic genes across general hypertension, hypertension with left ventricular remodeling, and uncontrolled hypertension - Yu, Chun-yang; Gu, Yang; Jiang, Yi-cheng; Zhang, Xi-wen (Frontiers in Cardiovascular Medicine, 2022)
The purpose of the present paper is to identify intrinsic genes across general hypertension, hypertension with left ventricular remodeling and uncontrolled hypertension. Four microarray datasets (GSE24752, GSE75360, GSE74144, and GSE71994) were downloaded from GEO database and conducted to detect differentially expressed genes (DEGs), respectively. Furthermore, gene set enrichment analysis (GSEA) was utilized to screen enriched biological pathways across four datasets above, respectively. And then, weighted gene co-expression network analysis (WGCNA) and functional enrichment were applied to screen out gene modules of interest and potential biological functions. Finally, Metascape-based multiple gene list meta-analysis was used to investigate intrinsic genes at different stages of the progression of hypertension. A total of 75 DEGs (63 upregulated genes and 12 downregulated genes, GSE24752) and 23 DEGs (2 upregulated genes and 21 downregulated genes, GSE74144). However, there were few DEGs identified in GSE75360, GSE71994, and part of GSE74144 datasets. GSEA and functional enrichment of gene module of interest have indicated that “Heme metabolism”, “TNF alpha/NFkB” and “interferon alpha response signaling”, MYC target v1/v2, were enriched significantly in different stages of hypertension progression. Significantly, findings from multiple gene list meta-analysis suggested that FBXW4 and other 13 genes were unique to hypertension group, TRIM11 and other 40 genes were mainly involved in hypertension with left ventricular remodeling group, while the other 18 genes including F13A1 significantly enriched in uncontrolled hypertension. Collectively, the signal conversion of “immune-metabolic-inflammatory” loop pathway was the most significant hallmark of in different stages hypertension, and provides a potential therapeutic target for hypertension treatment.